Implementation of corporate income tax accounting in an efffort to encourage corporate taxpayer compliance - Firdaus, Evan; Lestarie, Lieta Chiayu (ARKA INSTITUTE, 2022)
This paper aims to describe the implementation of tax accounting for corporate income tax and efforts to encourage corporate taxpayer compliance at the West Java Dispenda Big Family Cooperative. The method used is a case study with a quantitative approach, and the data collection used interview technique and documentation. Based on the results of the writing, the West Java Dispenda Big Family Cooperative has far used Final Income Tax calculation rate of 0.5% for Corporate Income Tax. The author has made comparison of Cooperative PHU Report 2018 - 2020 which has been carried out fiscal reconciliation. With the results of the analysis, the rate is more profitable if you use the calculation rate based on PP Number 23 of 2018 concerning Income Tax with a final rate of 0.5% of Taxable Income. So far, KKBD West Java has never been Underpaid and has always been on time in paying its taxes and reporting Tax Returns. Because the West Java KKBD only uses Commercial Financial Statements, the tax fee is quite large, and must make Fiscal Financial Statements. It can be concluded that can be done in order to ease the tax burden by utilizing tax incentives provided by the government.